Catalytic Mechanisms of Direct Pyrrole Synthesis via Dehydrogenative Coupling Mediated by PNP-Ir or PNN-Ru Pincer Complexes: Crucial Role of Proton-Transfer Shuttles in the PNP-Ir System - Qu, Shuanglin; Dang, Yanfeng; Song, Chunyu; Wen, Mingwei; Huang, Kuo-Wei; Wang, Zhi-Xiang (Journal of the American Chemical Society, 2014)
Kempe et al. and Milstein et al. have recently advanced the dehydrogenative coupling methodology to synthesize pyrroles from secondary alcohols (e.g., 3) and β-amino alcohols (e.g., 4), using PNP-Ir (1) and PNN-Ru (2) pincer complexes, respectively. We herein present a DFT study to characterize the catalytic mechanism of these reactions. After precatalyst activation to give active 1A/2A, the transformation proceeds via four stages: 1A/2A-catalyzed alcohol (3) dehydrogenation to give ketone (11), base-facilitated C–N coupling of 11 and 4 to form an imine-alcohol intermediate (18), base-promoted cyclization of 18, and catalyst regeneration via H2 release from 1R/2R. For alcohol dehydrogenations, the bifunctional double hydrogen-transfer pathway is more favorable than that via β-hydride elimination. Generally, proton-transfer (H-transfer) shuttles facilitate various H-transfer processes in both systems. Notwithstanding, H-transfer shuttles play a much more crucial role in the PNP-Ir system than in the PNN-Ru system. Without H-transfer shuttles, the key barriers up to 45.9 kcal/mol in PNP-Ir system are too high to be accessible, while the corresponding barriers (<32.0 kcal/mol) in PNN-Ru system are not unreachable. Another significant difference between the two systems is that the addition of alcohol to 1A giving an alkoxo complex is endergonic by 8.1 kcal/mol, whereas the addition to 2A is exergonic by 8.9 kcal/mol. The thermodynamic difference could be the main reason for PNP-Ir system requiring lower catalyst loading than the PNN-Ru system. We discuss how the differences are resulted in terms of electronic and geometric structures of the catalysts and how to use the features in catalyst development.